2009
DOI: 10.1103/physrevlett.102.245004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Polarization Force on Dust Acoustic Waves

Abstract: The effect of the polarization force acting on the grains in a nonuniform plasma background on the propagation of low-frequency waves in complex (dusty) plasmas is analyzed. It is shown that polarization interaction leads to a renormalization (decrease) of the dust acoustic phase velocity. The effect becomes more pronounced as the grain size increases. Finally, there is a critical grain size above which the dust acoustic waves cannot propagate, but aperiodic (nonpropagating) perturbations form instead.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
135
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(142 citation statements)
references
References 31 publications
7
135
0
Order By: Relevance
“…Most of these effects can be relatively easily included into the conventional fluid formalism, for some relevant examples we refer to Refs. [63][64][65][66][67][68][69][70]. Thus, careful analysis of the most important processes in each concrete practical situation is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these effects can be relatively easily included into the conventional fluid formalism, for some relevant examples we refer to Refs. [63][64][65][66][67][68][69][70]. Thus, careful analysis of the most important processes in each concrete practical situation is required.…”
Section: Discussionmentioning
confidence: 99%
“…The polarization force is small in most practical situations occurring in complex (dusty) plasmas, but can affect considerably the dispersion of dust acoustic waves as has been pointed out in Ref. [67].…”
mentioning
confidence: 97%
“…As shown by Khrapak et al [5] for Boltzmannian electrons and ions, the polarization force can be written as…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the parameter R = F p /F e represents the relative importance of the polarization force. Using such a model form of the polarization force, Khrapak et al [5] demonstrated that the polarization effect can play an important role in the propagation characteristics of the linear low-frequency DAWs. In particular, the polarization effect causes a decrease of the wave phase velocity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation